(untitled) (TEL Tempo, Espaço e Linguagem, 2016)
A pesquisa consiste num panorama histórico-cultural acerca da formação e consolidação da Literatura Brasileira partindo das tônicas essenciais de autonomia literária e nacionalismo tendo em vista a consolidação do projeto de cânone romântico brasileiro e pelas movimentações promovidas por intelectuais tais como José de Alencar (1829-1877) e Gonçalves Dias (1823-1864). Abstract: The research consists of a cultural historical panorama about the formation and consolidation of the Brazilian literatura with such autonomy literary, as well as nationalim with a view to the consolodation of the draft movement promoted by brazilian intelectual of romantic canon essential features such as José de Alencar (1829-1877) and Gonçalves Dias. Keywords: Canon. History of literature. Portuguese Language. Brazilian. Literature Portuguese Language. Romanticism. Resumen: Esa investigación consiste en presentar un panorama histórico cultural acerca de la formación y consolidación de la Literatura Brasileña con características específicas tales como la autonomía literaria y el nacionalismo los cuales se pretendían la consolidación del proyecto de constitución de un Canon romántico brasileño, movimiento promovido por intelectuales nacionalistas tales como José de Alencar (1829-1877) y Gonçalves Dias (1823-1864). Palabras clave: Historia de la literatura. Literatura brasileña. Romanticismo. Canon. Idioma Portugués.